Burrowing through the Heterogeneity: Review of Mouse Models of PTCL-NOS - Cutucache, Christine E.; Herek, Tyler A. (Frontiers in Oncology, 2016)
Currently, there are 19 different peripheral T-cell lymphoma (PTCL) entities recognized by the World Health Organization; however, 70% of PTCL diagnoses fall within one of three subtypes [i.e., peripheral T-cell lymphoma not otherwise specified (PTCL-NOS), anaplastic large-cell lymphoma, and angioimmunoblastic T-cell lymphoma]. PTCL-NOS is a grouping of extra-thymic neoplasms that represent a challenging and heterogeneous subset of non-Hodgkin’s lymphomas. Research into peripheral T-cell lymphomas has been cumbersome as the lack of defining cytogenetic, histological, and molecular features has stymied diagnosis and treatment of these diseases. Similarly, the lacks of genetically manipulated murine models that faithfully recapitulate disease characteristics were absent prior to the turn of the century. Herein, we review the literature concerning existing mouse models for PTLC-NOS, while paying particular attention to the etiology of this heterogeneous disease.